The study on the morphological changes of oropharynx in patients with complete unilateral cleft lip and palate after palatopharyngeal closure - Chen, Baitong; Zhang, Hongchuang (Frontiers in Neuroscience, 2022)
Cleft lip and palate can be treated as one of the most common craniofacial congenital malformations in humans. Such disease influences tens of millions of patients all over the world. Cleft lip and palate deformity affects many important physiological functions, including breathing, swallowing, speech, chewing, and aesthetics. This work focuses on investigating the morphology and airway volume of oropharynx patients with unilateral complete cleft lip and palate after palatopharyngeal closure. In addition, this work evaluated the similarities and differences between patients with cleft lip and palate and those without such an issue. The employed data, selected from the Department of Stomatology of Xuzhou First People's Hospital, are based on the conical beam CT images. The study sample was divided into two groups: the selected experimental group, who confronted the cleft lip, cleft palate, and velopharyngeal closure surgery, and the selected control group, who are healthy children at the corresponding age. The parameters, including the airway volume, the airway volume of velopharyngeal and oropharyngeal segments, the minimum cross-sectional area of the pharynx, the horizontal plane airway area of the hard palate and soft one, the horizontal airway area of the hyoid bone, and the vertical distance between the hard palate and soft palate, can be measured by Dolphin. These parameters were analyzed with a statistical approach. The analysis of the above-mentioned parameters reveals that the airway volume, the minimum cross-sectional area of the pharynx, the horizontal cross-sectional area of the hyoid, and the distance between the hard palate and soft palate tip in patients with complete unilateral cleft lip and palate show significant differences between the experimental group and the control group. Meanwhile, other parameters, including the horizontal cross-sectional area of the airway in the horizontal plane of the hard palate and the horizontal plane of the soft palate, did not show noticeable differences in the two groups. The patients, who confronted the unilateral complete cleft lip and palate, can improve with the velopharyngeal closure surgery. Furthermore, the length and vertical distance of the soft palate and the volume of each segment of the airway exhibit differences between the experimental group and the control group.